1130. Low Risk of Pneumocystis jiroveci Pneumonia in Patients With Waldenstrom's Macroglobulinemia on Ibrutinib. (26th November 2018) - Kusztos, Amanda E; Cheng, Matthew P; Gustine, Joshua N; Dubeau, Toni E; Woolley, Ann E; Hammond, Sarah P; Baden, Lindsey R; Castillo, Jorge J; Issa, Nicolas C
Abstract: Background: Ibrutinib is a Bruton's tyrosine kinase inhibitor that is FDA approved for the treatment of chronic lymphocytic leukemia (CLL), mantle cell lymphoma, marginal zone lymphoma, and Waldenstrom's macroglobulinemia (WM). Fungal infections including Pneumocystis jiroveci pneumonia (PCP) are increasingly reported in patients with CLL and lymphoma on ibrutinib possibly due to the off-target effect of ibrutinib on the adaptive immune system. Whether this increased risk is due to the effect of ibrutinib alone or in combination with immune dysregulation due to underlying malignancy is unknown. The purpose of this study was to assess the incidence of PCP in patients with WM on ibrutinib therapy. Methods: A retrospective cohort study was performed of all patients with WM who initiated ibrutinib monotherapy at Dana-Farber Cancer Institute between July 1, 2015 and January 30, 2018. Baseline characteristics, laboratory parameters, previous and concomitant malignancy treatment regimens, and antimicrobial medications were collected by chart review. Patients were followed until April 1, 2018 for the development of PCP. Results: There were a total of 106 patients with WM on ibrutinib during the study period. Sixty-one (58%) were male, and the median age at initiation of ibrutinib was 69 years (range 43 – 89). Forty-six patients (43%) received prior therapy for WM, with a median of two previous treatment courses (range 1–6). Fourteen patients (13%) were on PCP prophylaxis for a combined duration of 8 person-years. No cohort patient developed PCP during the study period, which included 146 person-years of ibrutinib exposure. Three patients (3%) died due to disease progression ( n = 2) and E. coli sepsis ( n = 1). Conclusion: Patients with WM on ibrutinib monotherapy appear to have a different infectious risk profile than patients with CLL or lymphoma and do not have a high risk of developing PCP. These data suggest that PCP prophylaxis is likely not beneficial for patients with WM on ibrutinib. Disclosures: M. P. Cheng, Royal College of Physicians and Surgeons of Canada: Member, Salary. S. P. Hammond, Merck: Investigator, Research support. J. J. Castillo, Pharmacyclics: Consultant and Grant Investigator, Consulting fee and Research grant. N. C. Issa, GSK: Investigator, Research grant. Merck: Investigator, Research grant. Akros Pharma: Consultant, Consulting fee.